2022
DOI: 10.1111/odi.14301
|View full text |Cite
|
Sign up to set email alerts
|

Oral leukoplakia diagnosis and treatment in Europe and Australia: Oral Medicine Practitioners' attitudes and practice

Abstract: The management of oral potentially malignant disorders (OPMD) including oral leukoplakia (OL) is not currently structured according to agreed guidelines. The current report presents survey data gathered from Oral Medicine Practitioners (OMPs) in Europe and Australia and is aimed to investigate attitudes and practice in the diagnosis, risk stratification and treatment of OL. In the presence of a clinical provisional diagnosis of OL, respondents reported always undertaking biopsy in 83% of cases, with most OMPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…The presence of OED already identifies a subgroup of patients with a high risk of progression to cancer; but finding a biomarker able to detect patients earlier with chromosome instability (CIN)—and for this reason more prone to develop OED itself—would be of utmost value and would allow an even earlier stratification of patients. Currently, no single reliable biomarker is available; clinicians usually consider together several patient‐ and lesion‐related features aimed at stratifying the risk of progression in a single patient; and biomarkers' assessment has still not entered the routine clinical‐practice of Oral Medicine Practitioners (OMPs) 51 . Most studies assessing the predictive value of the DNA ploidy status concluded that it has limited value in predicting progression to cancer as a single biomarker 16,17,20,21 ; the combined use of OED and DNA ploidy has been shown to be a better predictor for identifying low‐risk lesions 18,22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of OED already identifies a subgroup of patients with a high risk of progression to cancer; but finding a biomarker able to detect patients earlier with chromosome instability (CIN)—and for this reason more prone to develop OED itself—would be of utmost value and would allow an even earlier stratification of patients. Currently, no single reliable biomarker is available; clinicians usually consider together several patient‐ and lesion‐related features aimed at stratifying the risk of progression in a single patient; and biomarkers' assessment has still not entered the routine clinical‐practice of Oral Medicine Practitioners (OMPs) 51 . Most studies assessing the predictive value of the DNA ploidy status concluded that it has limited value in predicting progression to cancer as a single biomarker 16,17,20,21 ; the combined use of OED and DNA ploidy has been shown to be a better predictor for identifying low‐risk lesions 18,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive data from the literature, and although it is a more objective technique than OED evaluation, DNA ploidy status, evaluated either by Image or Flow Cytometry (ICM or FCM), is currently routinely assessed in practice by just under 10% of OMPs in Europe and Australia. 51 This could be related to a number of issues: the cost for each test (not greater than €50) is not prohibitive, but both ICM and FCM require facilities unavailable in most laboratories; and, primarily, the prospective validation of a strong predictive role of DNA ploidy is still lacking. Cox regression models based on our results show that DNA aneuploidy might not be as strong predictor as the other variables.…”
Section: Dna Ploidy Status In Olmentioning
confidence: 99%
“…The role of alcohol in the development of oral leukoplakia is less clear [7][8][9][10][11]. Some authors agree that the combination of tobacco and alcohol does increase the risk of malignant transformation, and that this is probably related (1) to the increased solubility of carcinogens and atrophy of the oral mucosa caused by alcohol, (2) to the mutagenic agents generated in metabolism (acetaldehyde), and (3) to the decreased DNA capacity associated with alcohol consumption [2,10].…”
Section: Introductionmentioning
confidence: 99%
“…The management of oral potentially malignant disorders (OPMD), including oral leukoplakia (OL), is controversial [ 1 , 2 , 3 ]. Among OPMD, oral leukoplakia remains the most commonly encountered condition in clinical practice [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation